The effect of strengthening exercise on the balance of athletes with chronic ankle instability: a literature review - Nadia Geovany Aritonang; W. Wahyuni (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: Repetitive ankle sprains can cause chronic ankle instability. More than 40% of athletes experience repeated ankle sprains and tend to be indifferent to these conditions, causing a decrease in ability when exercising or competing due to deficits in lower leg muscle strength, especially ankle propulsion, neuromuscular, proprioceptive, and postural control. Objective: to determine the effect of strength exercise on athletes with chronic instability ankle conditions. Method: the method used is a literature review or reviewing several articles that have been published. Results: The seven journals discussed show that strength exercise can improve the balance of athletes with chronic stability ankle conditions, and there are also several combinations of using tools such as resistance bands and blood flow restriction cuffs that make strength exercise more effective in improving the balance of athletes with chronic stability ankle conditions. Conclusion: There is an effect of strengthening exercises on the balance of athletes with chronic ankle instability.